Prognostic and Predictive Models for Left- and Right- Colorectal Cancer Patients: A Bioinformatics Analysis Based on Ferroptosis-Related Genes - Chen, Yingying; Li, Hua (Frontiers in Oncology, 2022)
Abstract Background: Left- and right-sided colorectal cancer (LCRC, RCRC) are significantly different in epidemiology and clinical manifestations and have altered outcomes. However, as a hot tumor prognostic marker, the role of ferroptosis-related genes (FRGs) in LCRC and RCRC is unknown. Methods: From The Cancer Genome Atlas (TCGA) database, we downloaded the expression profiles of CRC patients. A "DESeq2" package was performed to compare the differentially expressed genes (DEGs) of LCRC and RCRC. FRGs were identified using the FerrDb. The prognostic value of differentially expressed FRG (DE-FRG) in left- and right-CRC was assessed separately by Cox regression analysis. Subsequently, functional enrichment analysis, ESTIMATE, and single sample Gene Set Enrichment Analysis (ssGSEA) were performed based on LCRC and RCRC samples to reveal the potential function of FRGs-related risk signatures. The differential expression of differentially expressed ferroptosis-related genes in tumor tissues and adjacent normal tissues were verified by Western blot. The differential expression and prognosis in LCC and RCC were verified by immunohistochemistry. Results: Based on the identified 14 DE-FRGs, the LCRC prognostic model consisted of NOS2 and IFNG; NOS2 and ALOXE established the prognostic signature that could distinguish RCRC outcomes. In the functional analysis, the DEGs (high risk vs. low risk) of the LCRC and RCRC were significantly enriched in the immune- and lipid-related terms and pathways. ESTIMATE and ssGSEA suggested that these FRGs-related risk signatures were affiliated with the infiltration of immune cell subtypes. Finally, the mutation analysis revealed that FRGs-related risk signatures were unrelated to tumor mutation burden (TMB) in CRC patients. Western blotting results showed that NOS2 and ALOXE3 were significantly highly expressed in cancer, and the difference was statistically significant (P < 0.05). Immunohistochemical results showed that ALOXE3 was highly expressed in RCC, and those with high expression had a worse prognosis, while NOS2 gene had an effect on the prognosis of both LCC and RCC. Conclusion: This study constructed a potential prognostic model of LCRC and RCRC, respectively. We also identified the crucial pathways that contribute to elucidating the pathogenesis of CRC. Keyword: Colorectal cancer (CRC); Left- and right-sided; Prognosis; Ferroptosis-related genes (FRGs); Tumor microenvironment (TME)